Adolescent and young adult male chimpanzees form affiliative, yet aggressive, relationships with females. Issue 144 (July 2020) - Reddy, Rachna B.; Mitani, John C.
Abstract: Primates frequently form affiliative relationships that have important fitness consequences. Affiliative relationships between unrelated males and females are ubiquitous in humans but are not widely reported in humans' closest living relatives, chimpanzees (Pan troglodytes ). Instead, adult male chimpanzees are extremely aggressive to females, using the aggression to coerce females to mate with them. Adolescent male chimpanzees are physically and socially immature and unable to use aggression toward females in the same way as adult males. Instead, adolescent males might build affiliative relationships with females as an alternative tactic to increase their chances of mating and reproducing. To investigate this possibility, we recorded social interactions between 20 adolescent and 10 young adult males and 78 adult female chimpanzees over 2 years at Ngogo in Kibale National Park, Uganda. Analyses using grooming and proximity as assays revealed that adolescent and young adult males formed differentiated, affiliative relationships with females. These relationships were as strong as the bonds young males formed with maternal kin and unrelated males and increased in strength and number as males aged and started to dominate females. Male-female relationships extended outside the immediate context of mating. Although males affiliated slightly more often with females when they were cycling, they also did so when females were pregnant and nursing young infants. Males and females who formed bonds reassured each other, looked back and waited for each other while traveling, and groomed more equitably than other male-female pairs, even after the time they spent together in association and the female's reproductive state were taken into account. Despite the affiliative nature of these relationships, adolescent and young adult males selectively targeted their female partners for aggression. These findings provide new insights into the evolution of social bonds between human females and males, which can involve both affiliation and coercive violence. Highlights: Adolescent and young adult male chimpanzees form affiliative relationships with females similar to, yet different from, bonds adult male chimpanzees form with other males and maternal kin. As males enter adulthood, they form stronger relationships with more females than males do during adolescence. Adolescent and young adult males direct aggression selectively to females with whom they form affiliative social bonds.